Weighted Opial-type Inequalities for Fractional Integral and Differential Operators Involving Generalized Mittag Leffler Functions (European Journal of Pure and Applied Mathematics, 2017)
In this paper, by using Holder integral inequality we give generalization of weighted Opial-type inequalities by using generalized fractional integralÂ and differential operators involving generalized Mittag-Leffler functions.